Correlation Study Between Erythrocyte Acetylcholinesterase Activity, Serum Malondialdehyde and Insulin Sensitivity in Agricultural Workers and Non-agricultural Workers in Nat-Kan Village, Magway Township - Phyu, Mya Pwint; Hlain, Zarchi Theint Theint; Zaw, Thurein; Htway, Soe Minn; Sein, Mya Thanda (Journal of the ASEAN Federation of Endocrine Societies, 2020)
Objective. This study determined the correlation between erythrocyte acetylcholinesterase (AChE) activity, serum malondialdehyde (MDA) and insulin sensitivity in agricultural workers and non-agricultural workers. Methodology. The cross-sectional comparative study was undertaken in 45 agricultural and 45 non-agricultural workers from Nat-Kan Village, Magway Township. Erythrocyte acetylcholinesterase activity and serum malondialdehyde were measured by spectrophotometric method. Insulin sensitivity was calculated by homeostasis model assessment (HOMA-IR). Results. Mean erythrocyte AChE activity was significantly lower in agricultural (3553.99 IU/L) compared with nonagricultural workers (4432.68 IU/L) (p<0.001). A significant high level of mean serum MDA was observed in agricultural workers (0.74 versus 0.28 μmol/L, p<0.001). Median HOMA-IR value was significantly higher in agricultural (2.74) than that of non-agricultural workers (2.28) (p<0.05). The risk of insulin resistance was 2.8 times greater in agricultural workers than non-agricultural workers (OR 2.8, 95% CI, 1.18 to 6.72). Erythrocyte AChE activity had weak negative correlation with serum MDA level (r=-0.357, p<0.001) and HOMA-IR (ρ= 0.305, p<0.05). There was a significant but weak positive correlation between serum MDA level and HOMA-IR (ρ=0.355, p<0.001). Conclusion. Organophosphate pesticide exposure lowered erythrocyte AChE activity and increased oxidative stress. Oxidative stress is partly attributed to the development of insulin resistance.